Assessment Of Force Required During Cutting Oil Palm Fronds - Ishak, Khairul Aiman (Universiti Sains Malaysia, 2021)
The major activity in an oil palm plantation is oil palm harvesting, which demands a lot of energy, especially when cutting the oil palm fronds. Since the beginning of oil palm cultivation in Malaysia, attempts have been made to develop better cutting equipment. Most of the cutting tools developers claimed that the built cutting tools can help to reduce the burden on the harvester, however not all the claims are true at all. In this experiment, there are 2 main objectives of the research. The first objective is to study the relationship between the heights of oil palm fronds (below 1 m, between 1 m and 2 m, and above 2 m) with the measurement of force to cut the fronds using the conventional chisel. Next to investigate the relationship between the designs of sickle (intervention ‘pelajak’ and conventional sickle) with the measurement of force to cut the oil palm fronds above than 2 m height. The experiment conducted revealed that cutting oil palm fronds on 3 different heights using conventional chisel has an influence on the measurement of force for both inexperienced and experienced subjects which the higher the level of oil palm fronds, the higher the measurement of force. Meanwhile, on cutting oil palm fronds above 2 m, the study revealed that using intervention ‘pelajak’ sickle required more cutting force than using conventional sickle for the inexperienced subject, while for the experienced subject the design of the sickle did not influence the measurement of cutting force. However, the analysis on the number of successful cuts and time taken to cut the fronds shows that the intervention ‘pelajak’ sickle was better than the conventional sickle.